2008
DOI: 10.1300/j069v27n01_05
|View full text |Cite
|
Sign up to set email alerts
|

Music Therapy

Abstract: Co-occurring mental illness and addiction is very common and results in worse treatment outcomes compared to singly diagnosed addicted individuals. Integrated treatment for co-occurring disorders is associated with better treatment outcomes; however there is a wide range of what is included in integrated treatment. Due to patient and staff interests, integrated treatment often includes complementary and alternative therapies, including music and art therapy. There is a need to study how these approaches effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…In these studies, the effect of each component of music, such as chord progression, has not been dissected. Other studies have revealed that music changes mental function36 and a number of those have measured and studied biological indicators, such as ERPs, report that listening to music does result in altered brain activity. Arikan et al reported that listening to well-known music promotes attention and increases the P300 amplitude of ERPs 22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the effect of each component of music, such as chord progression, has not been dissected. Other studies have revealed that music changes mental function36 and a number of those have measured and studied biological indicators, such as ERPs, report that listening to music does result in altered brain activity. Arikan et al reported that listening to well-known music promotes attention and increases the P300 amplitude of ERPs 22.…”
Section: Discussionmentioning
confidence: 99%
“…In such ways, music is thought to act strongly upon the psyche of the audience. In medicine, numerous studies have demonstrated the effectiveness of music therapy for mental disorders, including schizophrenia, depression, and dementia 36…”
Section: Introductionmentioning
confidence: 99%
“…By using a fiber-based approach, they show that dopaminergic drug effects on striatal BOLD signal varied as a function of FA in a pathway connecting the OFC with the amygdala. There are many studies showing the role of music therapy as an adjunct to addiction therapy as espoused by Ross et al [18]. In an attempt to understanding the mechanisms by which listening to music affects neurological processes, we are struck by the work of Steele et al [19], who found that early trained musicians had greater connectivity in the posterior mid-body/isthmus of the corpus callosum and that the beginning age of training and sensorimotor synchronization performance is linked to FA in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, results of a prospective non-naturalistic and non-randomized pilot study without a control group suggest that music therapy in severely impaired patients with co-occurring mental illness and addiction is beneficial [20].…”
Section: Discussionmentioning
confidence: 99%